2016
DOI: 10.1186/s12899-016-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA targeting NF-κB attenuates lipopolysaccharide-induced acute lung injury in rats

Abstract: BackgroundTo investigate the anti-inflammatory effects of specific small interfering RNA targeting NF-κB on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in rats.MethodAcute lung injury was induced in Sprague-Dawley rats by intraperitoneal injection with LPS (5 mg/kg), followed by immediate intratracheal instillation of siRNA targeting NF-κB p65 (40 μg/ml). Animals in each group were sacrificed at 1 h or 8 h after the instillation. Pulmonary histological changes were evaluated by hematoxylin-eosin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…TNF-α is known to activate two major signaling pathways, namely the NFκB and MAPK pathways. Both these pathways are widely recognized to mediate inflammation in various cell types and pathological conditions [ 21 , 54 ], and are also common putative targets for the treatment of conditions involving pulmonary inflammation including ALI/ARDS [ 55 , 56 , 57 , 58 ]. A similar mechanism of action has also been reported in tHGA-treated activated mast cells, which is associated with its anti-allergic effect via suppression of inflammatory mediators production [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is known to activate two major signaling pathways, namely the NFκB and MAPK pathways. Both these pathways are widely recognized to mediate inflammation in various cell types and pathological conditions [ 21 , 54 ], and are also common putative targets for the treatment of conditions involving pulmonary inflammation including ALI/ARDS [ 55 , 56 , 57 , 58 ]. A similar mechanism of action has also been reported in tHGA-treated activated mast cells, which is associated with its anti-allergic effect via suppression of inflammatory mediators production [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a family of DNA binding proteins involved in the expression of pro-inflammatory factors and thus the development of ARDS. Depletion of NF-κB by specific siRNA targeted NF-κB p65 in lipopolysaccharide (LPS)-induced ALI rat models effectively reduced levels of the pro-inflammatory cytokines and ameliorated symptoms induced by LPS (97). In vivo administration of the siS1PLyase/HMGB1A/R3V6 complex reduced the S1PLyase level and weakened the inflammatory response and apoptosis in an LPS-induced ALI model, indicating that siS1PLyase and HMGB1A have a synergistic therapeutic effect for ALI (98).…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…In that, it has been demonstrated that the up-regulation of AhR and NF-jB promotes oxidative stress and apoptosis in cancer and non-cancer human lung epithelial cells (Zhang et al 2015;Jaligama et al 2018). Moreover, AhR knockdown protected zebrafish against cardiac toxicity (Van Tiem and Di Giulio 2011), whereas, NF-jB knockdown protects the lung from lipopolysaccharideinduced inflammation in rats (Li et al 2016).…”
Section: Control (B)mentioning
confidence: 99%